Spectrum of Central Nervous System Tumours at Tertiary Care Centre in Nepal - Chaudhary, Pramod; Munakomi, Sunil; Joshi, Narendera; Khanal, Babita; Kafle, Prakash (Journal of College of Medical Sciences-Nepal, 2022)
Introduction Most of the Central Nervous System tumors are benign. There is increase in the incidence in recent days which might be due to improved diagnosis with advancement in the ancillary studies. This study aims to provide a single centre histopathological spectrum of tumor of CNS. Methods This is a retrospective cross-sectional study of 138 cases of CNS tumors managed surgically in the department of neurosurgery from 2017 to 2020.All the histological subtypes and grading were reviewed. Data of the study population were analysed using SPSS version 25 and Microsoft excel. All the patients were classified as per the 2007 World Health Organization classification of central nervous system tumors. Results A total of 138 cases were analysed.One hundred and thirteen constitutes brain tumors and remaining 25 constitute the spinal tumors. Of the total cases, 132 were primary CNS tumor and remaining six were secondary CNS tumor. In cranial, 61 (44.2%) were extra axial tumors. There were 122 low grade tumor and remaining 16 were high grade tumors. Tumors of neuroepithelial origin were the most common 54 (38.9%) CNS tumors followed by meningiothelial tumors 36 (26.0%).Tumor were equally distributed in both the sex.Mean age of study population was 37.38 years ranging from 0.5 years to 75 years. Conclusions The present study concludes that the most common CNS tumour at our centre were neuroepithelial tumor mainly pilocytic astrocytoma followed by meningothelial.